L’isomorfismo nel "Tractatus logico-philosophicus": il caso dell’identità - Conti, Ludovica (Philosophy Kitchen - Rivista di filosofia contemporanea, 2017)
The notion of isomorphism provides an important key to understand the picture theory of language, as given in Tractatus logico-philosophicus. This paper discusses the thesis of isomorphism between language and world, surveying a particular issue of Wittgenstein’s proposal, that is the issue about the notion of identity: if we accept an interpretation of the picture-theory as based on the isomorphism between the world and the language, the refusal of identity’s sign (as predicative term of the language) have to correspond to a parallel metaphisical rejection. This paper argues that this metaphysical rejection concern Leibniz’s law about the identity of indiscernibles.